Edukasi Dampak Minuman Keras di Kalangan Remaja - Oemara Syarief, Amiroel; Pratiwi, Merina; Urva, Gellysa (Literasi Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
The modern transformation of habits from traditional habits brings about changes in people's habits in various aspects of life. Social change creates a discrepancy between elements or social elements so that deviant behavior arises. Deviant behavior makes teenagers who can fall into negative things, one of which is liquor. Adolescent orientation is just looking for pleasure and requires inner pleasure to eliminate saturation and fill free time in the evening so they prefer to go to karoke and nightlife as an alternative place to hang out with friends. Devotional activities are carried out using the method of lectures and discussions accompanied by Q&A. The achievement of community service is seen from changes in attitudes and behavior, because they have known about liquor, the factors behind someone trying liquor, the consequences caused by liquor, and legal sanctions.